N-Heterocycles as Cytotoxic Agents - Toreshettahally R. Swaroop; Kereyagalahally H. Narasimhamurthy; Muddegowda Umashankara; Kanchugarakoppal S. Rangappa (Novel Aspects on Chemistry and Biochemistry Vol. 6, 2023)
Synthesis of various nitrogen containing heterocyclic compounds such as benzimidazoles, quinazolines and pyrrolo [2,3-d]pyrimidines and their cytotoxicity against various cancer cell lines are presented in this chapter. These classes of compounds could emerge as potential anticancer agents.